Greasing, rent-seeking bribes and firm growth: evidence from garment and textile firms in Vietnam. - Nguyen, Thang V.; Le, Ngoc T. B.; Dinh, Ha L. H.; Pham, Huong T. L. (Crime, Law & Social Change, 2020)
Empirical studies on firm bribery do not distinguish different types of bribes. This obscures the complexity of bribes and contributes to the inconclusive findings on firm bribe–performance relationships. This study examines how greasing and rent-seeking bribes relate to firm growth in Vietnam. Based on data from a sample of garment and textile firms, the research shows that greasing bribes have a positive relationship with firm growth. By contrast, the relationship between rent-seeking bribes and firm growth is positive for state-owned firms, but not clear for private firms. The results suggest that anti-corruption strategies need to address the multifaceted nature of corruption.